2021
DOI: 10.3389/fpsyg.2021.647473
|View full text |Cite
|
Sign up to set email alerts
|

Music Listening in Times of COVID-19 Outbreak: A Brazilian Study

Abstract: The COVID-19 outbreak required diverse strategies, such as social distancing and self-isolation, to avoid a healthcare system crisis. However, these measures have been associated with the onset or increase of anxiety and depression symptoms in the population. Music listening was previously shown to regulate emotion, consequently reducing depression symptoms. Since previous studies with Brazilian samples have already shown a high prevalence of depressive symptoms during the first confinement period, the aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 67 publications
3
24
0
Order By: Relevance
“…In addition, a stronger correlation between SLC and "moderate emotion" during SiP than before SiP suggests a general increase in the need for music as a support tool to deal with the pandemic-induced stress. This agrees with the recently reported positive role of music listening for emotion regulation and venting negative emotion during the pandemic (Herrero et al, 2020;Carlson et al, 2021;Ferreri et al, 2021;Granot et al, 2021;Krause et al, 2021;Mak et al, 2021;Martín et al, 2021;Martínez-Castilla et al, 2021;Ribeiro et al, 2021b;Vidas et al, 2021;Ziv and Hollander-Shabtai, 2021).…”
Section: Stresssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, a stronger correlation between SLC and "moderate emotion" during SiP than before SiP suggests a general increase in the need for music as a support tool to deal with the pandemic-induced stress. This agrees with the recently reported positive role of music listening for emotion regulation and venting negative emotion during the pandemic (Herrero et al, 2020;Carlson et al, 2021;Ferreri et al, 2021;Granot et al, 2021;Krause et al, 2021;Mak et al, 2021;Martín et al, 2021;Martínez-Castilla et al, 2021;Ribeiro et al, 2021b;Vidas et al, 2021;Ziv and Hollander-Shabtai, 2021).…”
Section: Stresssupporting
confidence: 92%
“…For example, music listening time has typically increased during the pandemic (Cabedo-Mas et al, 2021;Carlson et al, 2021;Fink et al, 2021;Hurwitz and Krumhansl, 2021). The increase may be related to another common finding that people listen to music more frequently to cope with stress, regulate moods and emotions, and connect with others during the pandemic than under usual circumstances (Cabedo-Mas et al, 2021;Fink et al, 2021;Granot et al, 2021;Henry et al, 2021;Krause et al, 2021;Ribeiro et al, 2021b;Vidas et al, 2021;Ziv and Hollander-Shabtai, 2021). Remarkably, there are similar observations worldwide, highlighting that music not only serves such functions but is also one of the most common methods for this purpose during the pandemic.…”
Section: Introduction 1the Pandemic and Shift In Our Musical Lifementioning
confidence: 99%
“…Use of music as a proxy for social interaction was overall more prominent in people experiencing positive emotions whereas those experiencing negative emotions relied on music for solitary emotion regulation (Fink et al, 2021; see also Ribeiro et al, 2021b). Whereas the latter group were most strongly dissociated on hedonic motivations like distraction, daydreaming, negative emotion venting, comfort, and stress reduction, the former group were most strongly dissociated on eudaimonic motivations like spiritual and aesthetic experience, cultural connection, and identification with the artists and others.…”
Section: Moderating Factorsmentioning
confidence: 97%
“…When asked directly, most participants reported increased music listening during lockdown (Cabedo-Mas et al, 2021;Carlson et al, 2021;Ferreri et al, 2021;Fink et al, 2021;Mas-Herrero et al, 2020;Ribeiro et al, 2021aRibeiro et al, , 2021bSteinberg et al, 2021;Ziv & Hollander-Shabtai, 2021)-paradoxically, also for Spotify (Hurwitz & Krumhansl, 2021). Individual differences are, however, substantial, and some studies found no to little change (Carlson et al, 2021;Krause et al, 2021;Ziv & Hollander-Shabtai, 2021).…”
Section: Pandemic Music Listeningmentioning
confidence: 99%
See 1 more Smart Citation